Empowering future nurse-educators - (:unkn) unknown (fi=Turun yliopisto|en=University of Turku|, 2024)
The aim of the New Agenda for Nurse Educator Education (New Nurse Educator) project was to harmonize and optimize the nurse educator education in Europe by developing and testing a programme for nurse educator education: “Empowering the nurse educators in the changing world” and building evidence about nurse educator competences and continuing education needs as well as share and develop good practices for nurse educator education. At the beginning of the project, there was no clear consensus about the qualification requirements or education of nurse educators in Europe. The world is changing, and prevalence of current health issues is estimated to increase due to population aging and emerging new health issues. The project was kick-started during Covid-19 pandemic, which underlined the need to increase both flexibility and clearer guidelines for education. This project was conducted in collaboration between six universities from five European Union countries. The partners represent different parts of Europe and they were all very keen on developing the evidence-based nurse educator education, which was a fruitful base for the collaborative project. Now, looking at the Empowering Future Nurse Educators, one of the key products of the Erasmus+ Funded project, it can be said, that the project has achieved its goals. We want to thank all the authors who have contributed to this book. We also thank our colleagues and students who have inspired us to write this book. We hope this book also inspires educators in their discussions of nursing education and their teaching of nursing. Only in this way can we promote high-quality evidence-based nursing education and high-quality patient care. On behalf of the editors and authors, I wish you great moments with this handbook.